PROTECTIVE ROLE OF ARTEMISIA AFRA AQUEOUS EXTRACT ON TISSUE ANTIOXIDANT DEFENSE SYSTEMS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Afolayan, Anthony Jide; Sunmonu, Taofik Olatunde (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Changes in antioxidant capacity in the body as a result of oxidative stress play an important role in the development of diabetic complications. The aim of this study was to evaluate the effect of aqueous extract of Artemisia afra Jacq. ex Willd. on antioxidant defense systems in the liver and kidney of streptozotocin–induced diabetic rats. Administration of the extract to diabetic rats for 21 days significantly reduced blood glucose levels and increased body weight. The diabetic animals exhibited decreased levels of glutathione reductase (GR), glutathione peroxidase (GPx), superoxide dismutase (SOD) and reduced glutathione (GSH) in the liver and kidney, which were restored to near normal levels following treatment with the herb. The increased levels of lipid peroxidation observed in the tissues of diabetic rats were also reverted back to near normalcy after administering the extract. These findings revealed the protective role of A. afra on tissues by reducing oxidative stress which could be attributed to its flavonoids content. The efficacy of the plant compared favourably well with glibenclamide, a standard hypoglycemic drug.